Adaptive iron utilization compensates for the lack of an inducible uptake system in Naegleria fowleri and represents a potential target for therapeutic intervention - Arbon, Dominik; Ženíšková, Kateřina; Mach, Jan; Grechnikova, Maria; Malych, Ronald; Talacko, Pavel; Sutak, Robert (PLOS Neglected Tropical Diseases, 2020)
Naegleria fowleri is a single-cell organism living in warm freshwater that can become a deadly human pathogen known as a brain-eating amoeba. The condition caused by N. fowleri, primary amoebic meningoencephalitis, is usually a fatal infection of the brain with rapid and severe onset. Iron is a common element on earth and a crucial cofactor for all living organisms. However, its bioavailable form can be scarce in certain niches, where it becomes a factor that limits growth. To obtain iron, many pathogens use different machineries to exploit an iron-withholding strategy that has evolved in mammals and is important to host-parasite interactions. The present study demonstrates the importance of iron in the biology of N. fowleri and explores the plausibility of exploiting iron as a potential target for therapeutic intervention. We used different biochemical and analytical methods to explore the effect of decreased iron availability on the cellular processes of the amoeba. We show that, under iron starvation, nonessential, iron-dependent, mostly cytosolic pathways in N. fowleri are downregulated, while the metal is utilized in the mitochondria to maintain vital respiratory processes. Surprisingly, N. fowleri fails to respond to acute shortages of iron by inducing the reductive iron uptake system that seems to be the main iron-obtaining strategy of the parasite. Our findings suggest that iron restriction may be used to slow the progression of infection, which may make the difference between life and death for patients.